A Diastereoselective Synthesis of Functionalized Tetrahydroindeno[2′, 1′, 3, 4]pyrido[2, 1‐a]isoquinolines. Issue 2 (February 2016) - Manouchehri, Arezoo Lazar; Mirzaei, Anvar; Yavari, Issa
Abstract: An effective route to alkyl 9a‐(2, 3‐dihydro‐1, 3‐dioxo‐1 H ‐inden‐2‐yl)‐9a, 14, 14a, 14b‐tetrahydro‐14‐oxoindeno[2′, 1′:3, 4]pyrido[2, 1‐ a ]isoquinoline‐9‐carboxylates via a diastereoselective one‐pot four‐component reaction of isoquinoline and alkyl prop‐2‐ynoates with two equivalents of indane‐1, 3‐dione, in aqueous MeOH at room temperature, is described. Abstract :